Successful Treatment of Severe Type B Lactic Acidosis in a Patient with HIV/AIDS-Associated High-Grade NHL. (13th September 2018) - Mejia, Marco; Perez, Ariel; Watson, Harold; Sanchez, Daniel; Parellada, Jorge; Madruga, Mario; Carlan, S. J.
Abstract : Type B lactic acidosis is a rare metabolic complication sometimes associated with hematologic malignancies. When present, this type of lactic acidosis is most commonly seen in patients with high-grade lymphomas or leukemias and is usually indicative of a dismal prognosis. We report a case of a 27-year man with acquired immunodeficiency syndrome (AIDS) that presented with bilateral lower extremity swelling, an abdominal mass, and weight loss. His lab values showed elevated anion gap with lactic acidosis and computed tomography (CT) of the abdomen showed a large soft-tissue mass arising from the left hepatic lobe. Biopsy of the abdominal mass demonstrated a high-grade diffuse large B-cell lymphoma. The patient's lactic acidosis resolved after starting chemotherapy, and a complete response was evident on PET-CT after a third cycle of rituximab, etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin (EPOC-RR). Care-givers should be aware of the implications of lactic acidosis associated with malignancy and the need for prompt diagnosis and treatment.